The Influence of Product Quality, Price, and Lifestyle on the Decision to Purchase Preloved Clothes in Tiktok Shop - Fhita Fhita; Andry Stepahnie Titing; Agus Zul Bay (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of product quality, price, and lifestyle on the purchase decisions of preloved clothing among Generation Z consumers on TikTok Shop in Kolaka Regency. With the growing popularity of social commerce and sustainable fashion trends, preloved or second-hand clothing has become an increasingly attractive option, particularly among younger, digitally engaged consumers. Using a quantitative approach, this study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationships between variables. Data were collected from 150 respondents through purposive sampling, targeting active TikTok users aged 18–27 who had previously purchased preloved clothing online. The findings reveal that all three independent variables—product quality, price, and lifestyle—have a positive and statistically significant effect on purchase decisions. Among them, lifestyle exerts the strongest influence (β = 0.42), suggesting that factors such as self-expression, social identity, peer influence, and alignment with current fashion trends play a crucial role in shaping Generation Z's purchasing behavior. Product quality (β = 0.31) and price (β = 0.29) also significantly impact decisions, reflecting the importance of perceived value and affordability in a competitive online market. The coefficient of determination (R² = 0.44) indicates that 44% of the variation in purchase decisions can be explained by the three variables. These results offer valuable insights for digital marketers, TikTok influencers, and preloved fashion entrepreneurs in designing more personalized, lifestyle-oriented, and value-driven marketing strategies. By aligning their campaigns with the identity-driven consumption patterns of Generation Z, businesses can strengthen customer engagement and drive purchase intentions in the evolving digital economy.